2021
DOI: 10.3168/jds.2020-19820
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of yogurts fermented with short-chain fatty acid-producing probiotics and their effects on mucin production and probiotic adhesion onto human colon epithelial cells

Abstract: Probiotics can ferment nondigestible carbohydrates and produce short-chain fatty acids (SCFA; acetate, propionate, and butyrate) in the human colon. In this study, the levels of SCFA were determined in the following yogurts fermented with different combinations of probiotics: (1) cocultures of Streptococcus thermophilus and Lactobacillus bulgaricus (control, C); (2) S. thermophilus, L. bulgaricus, and Bifidobacterium bifidum (C-Bb); (3) S. thermophilus, L. bulgaricus, and Lactobacillus acidophilus (C-La); and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Because SCFAs can be used as a fermentation source for other bacteria, supplementation with SCFA-producing bacteria is therefore a strategy to modulate the intestinal microbiome, increase endogenous SCFA production and restore dysbiosis [ 90 , 91 ]. In agreement, it has been shown that a yogurt diet rich in acetate could improve the protective function of the intestinal epithelium [ 92 ]. Likewise STH strain ST4 increases the fecal content of acetate in correlation with maintenance of inflammatory homeostasis and preservation of intestinal permeability in a mucositis induced model [ 61 ].…”
Section: Resultsmentioning
confidence: 58%
“…Because SCFAs can be used as a fermentation source for other bacteria, supplementation with SCFA-producing bacteria is therefore a strategy to modulate the intestinal microbiome, increase endogenous SCFA production and restore dysbiosis [ 90 , 91 ]. In agreement, it has been shown that a yogurt diet rich in acetate could improve the protective function of the intestinal epithelium [ 92 ]. Likewise STH strain ST4 increases the fecal content of acetate in correlation with maintenance of inflammatory homeostasis and preservation of intestinal permeability in a mucositis induced model [ 61 ].…”
Section: Resultsmentioning
confidence: 58%
“…Subsequently, S. thermophilus strains were further cocultured with L. bulgaricus in pasteurized milk. Streptococcus thermophilus and L. bulgaricus are closely related and have formed a complex symbiosis and antagonism relationship in milk (Chang et al, 2021). For example, S. thermophilus provides formic acid, folic acid, carbon dioxide, and long-chain fatty acid for L. bulgaricus, and L. bulgaricus provides peptides and AA for S. thermophilus (Markakiou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the transcriptional activation of HSP70 was proven to be related to the activation of mitogen-activated protein kinase (MEK)/ extracellular signal-regulated kinase (ERK) and mTOR pathways, as well as the inhibition of HDAC [ 76 ]. Besides, acetate increased the expression of MUC2 and CDX2, as well as the production of mucin proteins, in mucus-secreting colon epithelial cells (HT29-MTX), which indicated that it could improve the intestinal epithelium protective function [ 77 ]. SCFAs in an optimal dose could modulate the structure of gut microbiota, regulate the activities of immune cells and intestinal epithelial cells via regulating the gene expression of intestinal cells in an HDAC-dependent way, and subsequently improve the gut barrier function [ 58 ].…”
Section: The Bioactivities Of Scfasmentioning
confidence: 99%